1980
DOI: 10.1002/jez.1402140116
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of supernumerary limbs following blastemal rotations in the newt

Abstract: Experiments on the newt, Notophthalmus viridescens, showed that 180" surgical rotation of the forelimb blastema could provoke supernumerary limb formation (Bryant and Iten, '76). The polar coordinate model predicts a high incidence of supernumerary limbs for angles of rotation at or near 180" and no supernumeraries for small angles of rotation. The results of recent experiments on axolotls (Maden and Turner, '78; Wallace, '78; Wallace and Watson, '79, Turner, pers. comm.), however, do not exhibit this pattern.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Meanwhile, several other investigations had reported that up to three supernumeraries arise after APDV rotation over a wide range of angles (Wallace, 1978;Maden, 1978b;Wallace and Watson, 1979), though the maximum frequency of formation was at 180 , falling off on either side (Stock et al, 1980;Turner, 1981). Furthermore, the loci of origin of these limbs were unpredictable.…”
Section: Models Of Pattern Formationmentioning
confidence: 98%
“…Meanwhile, several other investigations had reported that up to three supernumeraries arise after APDV rotation over a wide range of angles (Wallace, 1978;Maden, 1978b;Wallace and Watson, 1979), though the maximum frequency of formation was at 180 , falling off on either side (Stock et al, 1980;Turner, 1981). Furthermore, the loci of origin of these limbs were unpredictable.…”
Section: Models Of Pattern Formationmentioning
confidence: 98%
“…Notice that the mobility of bacteria was studied using PCS in detail [209,[218][219][220][221][222]. This ability of PCS is of importance in respect of elucidation of the influence of media or cryogel membrane or scaffolds on living microorganisms.…”
Section: Diffusion Of Small Molecules Polymers Proteins and Cells Wmentioning
confidence: 99%
“…Το μοντέλο όμως δεν μπορεί να εξηγήσει την εμφάνιση υπεραρίθμων στις διάφορες περιοχές της περιφέρειας μετά από περιστροφές μικρότερες ή μεγαλύτερες από 180 (Maden and Turner,1978;Stock et al,1980;Wallace and Watson,1979), ούτε τη δημιουργία συμμετρικών ως προς τους εγκάρσιους άξονες άκρων ή μεικτών μετά από περιστροφή 180 (Tank ,1981;Maden,1982;Maden and Mustafa,1982b;Papageorgiou and Holder, 1983). Επιπλέον αποτελέσματα μετά από περιστροφή 90 (Stock and Savage, 1978a, b;Maden, 1982Maden, ,1983a δεν επιβεβαιώνουν τις αρχές του μοντέλου.…”
Section: μοντελαunclassified